A Lifestyle Medicine Intervention to Reduce GERD Symptoms and Medication Use - Emily Senay; Maya Korin; Elizabeth Garland; Michael S. Smith; John D. Meyer (Lifestyle Medicine)
ABSTRACT Lifestyle modifications (LMs) are recommended as first‐line therapy for gastroesophageal reflux disease (GERD). This study aims to evaluate in a population with a high burden of GERD a lifestyle medicine intervention aimed at reducing GERD symptoms and medication use through patient‐driven health goal setting, health coaching, and SMART LM prescribing. First responders to the attacks at the World Trade Center on September 11, 2001 have a high GERD burden associated with exposures at Ground Zero and lifestyle. An LM GERD‐specific intervention, delivered virtually and integrating health technology for data capture, will be implemented in this cohort with the goal of reducing GERD symptoms and/or medication use. This study aims to investigate the value, feasibility, and satisfaction of full LM six‐pillar of health intervention that includes patient‐driven health goal setting and health coaching over a 6‐month period in the treatment of GERD. A nonrandomized, noncontrolled prospective intervention will be implemented in patients with GERD who expressed interest in LMs. All participants will complete a self‐administered (delivered via text) baseline American College of Lifestyle Medicine six‐pillars of health survey and monthly GERD‐Health Related Quality of Life (HRQL) symptom and medication use questionnaires. Participants will receive seven telemedicine visits over 6 months with LM physicians that will include an initial GERD history evaluation and health coaching on GERD‐specific modifications. Additionally, participants will self‐rate confidence in achieving three LM modifications of high interest and SMART prescriptions will be written. Monthly coaching sessions to monitor progress with LM modifications will be provided and progress tracked over the 6‐month study period. A satisfaction survey will be completed approximately 1 week after study completion. Outcome measures include GERD‐HRQL scores and medication use. Patient satisfaction, feasibility, and acceptability will be surveyed at the end of the intervention.